All Plant Breeding Technologies Are Equal, but Some Are More Equal Than Others: The Case of GM and Mutagenesis - Batalha, Luisa; Foroni, Francesco; Jones, Brian Joseph (Frontiers in Plant Science, 2021)
A pervasive opposition to genetically modified (GM) foods has developed from the notion that they pose a risk to human and environmental health. Other techniques for the genetic modification of plants, such as sexual crossing and mutagenesis breeding, have mostly remained unchallenged. This research aims to investigate public perception of plant breeding technologies. Specifically, sexual crossing, mutagenesis, transgenics (GM) and gene editing. It was expected that attitudes and intentions would be most positive and the perception of risk lowest for plant genetic modification through sexual crosses. Scores on these variables were expected to be similar between mutagenesis, GM and gene editing. It was also expected that attitudes, intentions and risk perception would change (becoming more positive) once participants learned about foods developed through these technologies. Participants reported their attitudes, intentions and risk perception at two points in time. At Time 2, they were presented with pictures of food items developed through sexual crossing, GM and mutagenesis. The results showed that mutagenesis stood out as the most negatively perceived technology, whereas genetic development via sexual crosses was generally perceived as positive. The results highlight the importance of messaging, framing and consumer attitudes.